Crime and Remittance Transfers. - Vargas-Silva, C (Palgrave Macmillan, 2009)
This article examines the determinants of remittance transfers, specifically focusing on the impact of crimes on remittances. Using the 2003 Quality of Life Survey of Colombia, we find that both domestic and international transfers are negatively affected by crime. That is, because crime may have an adverse effect on household assets and the return to investments in the home community, migrants may decrease transfers made for self-interested purposes such as future inheritance or investment. Although results suggest that a portion of transfers are sent for self-interest motives, variables related to the household indicate that altruism is also an important motivation for remitting.